Wine Retail Price Dispersion in the United States: Searching for Expensive Wines? - Jaeger, David A; Storchmann, Karl (American Economic Review, 2011)
Similar to other markets in which deviations from Jevons' “law of one price” is the norm rather than the exception, the retail wine market in the United States is characterized by large price dispersions. Drawing on a large sample of retail prices from wine-searcher.com we find an average per-wine coefficient of variation of 23 percent. Some of this is due to differential market conditions, especially state regulations. Our evidence suggests that dispersion also depends positively on price levels, after controlling for consumer, market, and state heterogeneity.